A instrumentalidade na formação profissional: breves reflexões a partir da experiência do curso de Serviço Social da UFT campus de Miracema - Rodrigues, Luzineide Ferreira de Sousa (Universidade Federal do Tocantins, 2020)
The present Course Conclusion Paper deals with the discussion of instrumentality in the vocational training in Social Work from the experience of UFT campus Miracema, a result of concerns in the training process, especially from the insertion in the supervised internship in Social Work. . With qualitative nature, the research had the general objective to analyze the teaching of instrumentality in the scope of the professional formation in Social Work from the experience of the UFT - Campus of Miracema do Tocantins. The methodological procedures were oriented from a critical perspective of reality analysis based on bibliographic, documentary and field research. The main categories presented are about work, instrumentality and professional training in Social Work. Although the limits for the analysis of the research findings, it is considered that the teaching of instrumentality in vocational training in UFT Social Work is linked to the perspective expressed in the training project with the curricular guidelines of ABEPSS.